PERTANGGUNGJAWABAN PIDANA TERHADAP PIHAK YANG IKUT SERTA DALAM TINDAK PIDANA TERORISME DI INDONESIA - Syavica, Zahrana; Saragih, Yasmirah Mandasari; Sihombing, August Saut Maringan; Israq, Yoldy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Terrorism constitutes a transnational crime that instills significant fear in society. As a crime against humanity, terrorism is categorized as an extraordinary crime due to its capacity to incite widespread chaos under the guise of religion, ideology, or organizational affiliation. In Indonesia, acts of terrorism are regulated under Law No. 5 of 2018 concerning the Eradication of Terrorism Crimes. The elusive and well-connected nature of terrorist networks makes their dismantling particularly challenging. The ease of cross-border movement further complicates efforts to disrupt these networks. Therefore, addressing terrorism effectively requires coordinated actions through bilateral, regional, and international cooperation. This study employs a normative legal research method, grounded in legal theory, using a legislative and literature-based approach. The objective of this research is to examine the underlying motivations that lead individuals to engage in terrorism and to analyze the framework of criminal liability for those who participate in acts of terrorism within Indonesia.Keywords: Criminal Law Accountability, Perpetrators, Crimes, Terrorism.